Susceptibility to Bismuth(III) of Aquaculture Bacterial Pathogens: Effectiveness of Bismuth–Deferiprone Therapy against Vibrio anguillarum Infection in Fish - Miguel Balado (MDPI AG, 2021)
Bismuth is a heavy metal with antibacterial properties that has a long history of medicinal use. The results reported here suggest that bismuth(III) (chelated with deferiprone) could be used in aquaculture systems to treat bacterial disease outbreaks, greatly reducing antibiotic use. We tested bismuth susceptibility in a collection of aquaculture bacterial pathogens. In the presence of bismuth concentrations ranging from 1.3 to 13 µM, most bacteria started showing a drastic decrease in their growth ability, although with high inter- and intraspecific variability. The minimal inhibitory concentrations of bismuth ranged from 13 to more than 780 µM, depending on bacterial species and strain. The results of in vivo assays suggest that low concentrations of bismuth could be especially effective to treat vibriosis caused by Vibrio anguillarum, since bismuth greatly reduced mortality in experimentally infected fish without any observable side effects. A bismuth therapy, alone or combined with other antimicrobials, could contribute to reduce the use of antibiotics in aquaculture.